Immunogenicity of a rheumatoid arthritis protective sequence when acquired through microchimerism - Kanaan, Sami B. (Proc Natl Acad Sci U S A, 2019)
HLA class II genes provide the strongest genetic contribution to rheumatoid arthritis (RA). HLA-DRB1 alleles encoding the sequence DERAA are RA-protective. Paradoxically, RA risk is increased in women with DERAA(+) children born prior to onset. We developed a sensitive qPCR assay specific for DERAA, and found 53% of DERAA(−/−) women with RA had microchimerism (Mc; pregnancy-derived allogeneic cells) carrying DERAA (DERAA-Mc) vs. 6% of healthy women. DERAA-Mc quantities correlated with an RA-risk genetic background including DERAA-binding HLA-DQ alleles, early RA onset, and aspects of RA severity. CD4(+) T cells showed stronger response against DERAA(+) vs. DERAA(−) allogeneic cell lines in vitro, in line with an immunogenic role of allogeneic DERAA. Results indicate a model where DERAA-Mc activates DERAA-directed T cells that are naturally present in DERAA(−/−) individuals and can have cross-reactivity against joint antigens. Moreover, we provide an explanation for the enigmatic observation that the same HLA sequence differentially affects RA risk through Mendelian inheritance vs. microchimeric cell acquisition.